Media Development for Brand Awareness and Added Value to Lak Roi Sesame Rice Crackers, Nakhon Ratchasima Province - Khamcharoen, Pheerawish; Buanak, Netchanok; Musakophas, Roongkan; Panomjerasawat, Jaruwan; Lawanna, Isarachai (Area Based Development Research Journal, 2023)
Lak Roi sesame rice crackers, Nonthai Sub-district, Nonthai District, Nakhonratchasima Province, was merely recognized among the local customers. The research study intends to develop media that communicate with broader communities and promote Lak Roi sesame rice crackers brand awareness through participatory action research conducted by communication academicians and community entrepreneurs. The processes include 1) Studying the context of Lak Roi sesame rice cracker entrepreneurs, 2) Collaboratively constructing Lak Roi sesame rice crackers identity, 3) Communal consideration of media design for Lak Roi sesame rice crackers, 4) Creating the media for Lak Roi sesame rice crackers, 5) Enhancing online marketing skills for Lak Roi sesame rice cracker entrepreneurs, and 6) Organizing exhibitions for Lak Roi sesame rice crackers with the entrepreneurs’ collaboration. The processes intended to create the online and offline media that show the product identity, and to run workshops for online marketing to enhance the skills and expand the customer base. Consequently, the media to communicate Lak Roi sesame rice crackers emerging from the project are the logo, the packaging, the label, the paper label attached to the top of the product package, the poster promoting Lak Roi sesame rice crackers on the Facebook Page, the video clip advertising Lak Roi sesame rice crackers and the product photos. These could add value to the product as well as raise brand awareness. In conclusion, the project leads to an increase of 50% in Lak Roi sesame rice crackers sales, and a monthly profit of 30,000 Baht, generating more income and developing the community economy.